Tungsten carbide modified nitrogen-doped hollow rod-like carbon material, and preparation method and application thereof

CN122426744BActive Publication Date: 2026-10-30GANNAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610903956.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-30
Estimated Expiration
2046-06-23

AI Technical Summary

Technical Problem

但是室温钠硫电池仍存在一系列挑战,例如,多硫化物穿梭效应、充放电过程中的体积膨胀以及硫本身导电性差等导致其面临倍率性能低、容量衰减快以及循环寿命短等问题

Benefits of technology

本发明通过氮掺杂有效增加了碳材料对多硫化物的化学吸附能力,有效抑制穿梭效应;且碳化钨纳米颗粒不仅提高电极的电导率,还为多硫化物的吸附和催化转化提供了丰富的活性位点,从而加快反应动力学过程,促进多硫化物的催化转化;同时碳化钨修饰的氮掺杂中空棒状碳材料具有较大的比表面积和丰富的微孔/介孔结构,能够实现高硫负载以及适应充放电过程中的体积膨胀;碳化钨纳米颗粒和氮掺杂的协同作用,进一步显著提升了碳框架的电导率以及对多硫化物吸附和催化转化能力,从而获得优异的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122426744B_ABST
    Figure CN122426744B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrochemical energy storage devices, and specifically discloses a tungsten carbide modified nitrogen-doped hollow rod-shaped carbon material, a preparation method and application thereof, and the preparation method comprises the following steps: dispersing zinc acetate dihydrate and sodium hydroxide in deionized water, adding glycerol to perform a hydrothermal reaction; dispersing zinc oxide, phosphotungstic acid and 2-methylimidazole in a mixed solution of deionized water and N,N-dimethylformamide to perform a self-assembly reaction through water bath heating; and performing carbonization treatment in an inert atmosphere. The tungsten carbide modified nitrogen-doped hollow rod-shaped carbon material, the preparation method and the application thereof are beneficial to the adsorption of polysulfides, can effectively inhibit the shuttle effect, promote the conversion between sulfur and polysulfides, and have the advantages of simple preparation method and low production cost. After the tungsten carbide modified nitrogen-doped hollow rod-shaped carbon material is compounded with sublimed sulfur to form a positive electrode material, a sodium-sulfur battery assembled therefrom has excellent cycle stability and rate performance, and is suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage device technology, and in particular to nitrogen-doped hollow rod-shaped carbon materials modified with tungsten carbide, their preparation methods and applications. Background Technology

[0002] With the development of electric vehicles and research into energy storage power stations, the market demand for high energy density is increasing, while also considering cost and environmental impact. Therefore, developing high-energy-density and low-cost energy storage devices is crucial. Room-temperature sodium-sulfur batteries (RT Na-S) are widely considered a promising next-generation energy storage system due to their advantages such as high theoretical specific capacity (1675 mAh / g), high energy density (1274 Wh / kg), abundant raw material reserves, and environmental friendliness. However, RTD Na-S batteries still face a series of challenges, such as the polysulfide shuttle effect, volume expansion during charge and discharge, and the poor conductivity of sulfur itself, leading to problems like low rate performance, rapid capacity decay, and short cycle life.

[0003] In existing technologies, the key step determining the overall reaction rate of room-temperature sodium-sulfur batteries lies in the conversion of sodium polysulfides: that is, the conversion of long-chain sodium polysulfides (Na2S) during discharge. x ,4< x <8) It is converted into short-chain sodium sulfide (Na2S2 / Na2S), and sodium sulfide is effectively converted into elemental sulfur during charging. Improving the conversion reaction kinetics of sodium polysulfide during charging and discharging is crucial for mitigating the "shuttle effect" of soluble sodium polysulfide.

[0004] Therefore, developing an efficient catalyst as a sulfur host for room-temperature sodium-sulfur batteries to alleviate polysulfide shuttle and accelerate its conversion reaction kinetics is crucial for improving the overall electrochemical performance of room-temperature sodium-sulfur batteries. Summary of the Invention

[0005] The purpose of this invention is to provide tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon materials, their preparation methods, and applications. These materials are beneficial for the adsorption of polysulfides, can mitigate the shuttle effect, and accelerate the conversion between sulfur and polysulfides. Furthermore, the preparation method is simple and the production cost is low. Sodium-sulfur batteries assembled from sublimed sulfur composite cathode materials exhibit excellent cycle stability and rate performance, making them suitable for large-scale applications.

[0006] To achieve the above objectives, the present invention provides tungsten carbide (WC) 1-x The method for preparing nitrogen-doped hollow rod-shaped carbon materials modified by nitrogen includes the following steps: S1. Disperse zinc acetate dihydrate and sodium hydroxide in deionized water according to the proportion, stir and mix, clarify and then add glycerol to carry out hydrothermal reaction to obtain rod-shaped zinc oxide (ZnO). S2. According to the proportion, zinc oxide, phosphotungstic acid and 2-methylimidazole obtained in S1 are dispersed in a mixed solution of deionized water and N,N-dimethylformamide, and a self-assembly reaction is carried out by water bath heating to obtain PTA@ZIF-8 / ZnO. S3. Place the PTA@ZIF-8 / ZnO obtained in S2 in an inert atmosphere and perform carbonization treatment to obtain nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide.

[0007] Preferably, in S1, the zinc acetate dihydrate is first dispersed in deionized water, then sodium hydroxide is added, stirred, and then glycerol is added; The ratio of zinc acetate dihydrate, deionized water, sodium hydroxide, and glycerol is 3.3g:45mL:12g:105mL.

[0008] Preferably, in S1, the hydrothermal reaction specifically comprises: After adding glycerol, the mixture was allowed to stand for 30 minutes, then placed in a reaction vessel and reacted at 140-160°C for 20 hours to obtain a precipitate. The precipitate was washed with deionized water until neutral and dried to obtain rod-shaped zinc oxide.

[0009] Preferably, in S2, the molar ratio of zinc oxide to phosphotungstic acid is 8.33~12.5:1; The molar ratio of zinc oxide to 2-methylimidazole is 1:4~6; The volume ratio of the deionized water to the N,N-dimethylformamide is 1:1 to 1.95.

[0010] Preferably, in S2, the heating temperature of the water bath heating self-assembly reaction is 70~80℃, and the heating time is 10~15h.

[0011] Preferably, in S3, the inert atmosphere is either argon or nitrogen.

[0012] Preferably, in S3, the specific conditions for the carbonization treatment are as follows: Heat to 850-950℃ at a heating rate of 3-5℃ / min, and hold for 1-3 hours.

[0013] The present invention also provides nitrogen-doped hollow rod-shaped carbon materials modified with tungsten carbide.

[0014] This invention also provides the application of tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon materials in the preparation of room-temperature sodium-sulfur batteries, wherein the room-temperature sodium-sulfur battery includes a room-temperature sodium-sulfur battery cathode material, and the preparation method of the room-temperature sodium-sulfur battery cathode material includes the following steps: According to the proportion, the nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide and sublimed sulfur are dispersed in a volatile organic solvent, ground, heated to 155~165℃ and kept at that temperature for 6~12h to obtain a room temperature sodium-sulfur battery cathode material.

[0015] Preferably, the mass ratio of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material to the sublimated sulfur is 1:1.2~2.0.

[0016] Preferably, the volatile organic solvent is carbon disulfide.

[0017] Therefore, the present invention utilizes the above-mentioned tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material, its preparation method, and its application, with the following beneficial effects: This invention effectively increases the chemical adsorption capacity of carbon materials for polysulfides through nitrogen doping, effectively suppressing the shuttle effect. Furthermore, tungsten carbide nanoparticles not only improve the conductivity of the electrode but also provide abundant active sites for the adsorption and catalytic conversion of polysulfides, thereby accelerating the reaction kinetics and promoting the catalytic conversion of polysulfides. Simultaneously, the nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide has a large specific surface area and abundant microporous / mesoporous structures, enabling high sulfur loading and adapting to volume expansion during charge and discharge. The synergistic effect of tungsten carbide nanoparticles and nitrogen doping further significantly enhances the conductivity of the carbon framework and its ability to adsorb and catalytically convert polysulfides, thus achieving excellent electrochemical performance.

[0018] The preparation process of this invention is simple and low in cost. When the cathode material prepared by combining it with sublimed sulfur is applied to room temperature sodium-sulfur batteries, it can significantly improve the cycle stability and rate performance of the batteries, and has good prospects for large-scale application.

[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the preparation process in Example 1; Figure 2 WC in Example 1 1-x Electron micrographs of / NHCR-150, where a is a scanning electron microscope (SEM) image at 1 μm, b is a SEM image at 100 nm, c is a transmission electron microscope (TEM) image at 1 μm, and d is a TEM image at 10 nm. Figure 3 WC in Example 1 1-x The nitrogen adsorption-desorption characterization results of / NHCR-150 are shown in Figure a, where a is the nitrogen adsorption-desorption isotherm and b is the pore size distribution curve. Figure 4 The TGA curve of the sodium-sulfur battery cathode material in Example 1; Figure 5 The graph shows the electrochemical performance test results of the CR2032 coin cell in Example 1. Figure 6 WC in Example 2 1-x SEM images of / NHCR-100, where a is the SEM image at 2μm and b is the SEM image at 100nm; Figure 7 The graph shows the electrochemical performance test results of the CR2032 coin cell in Example 2. Figure 8 The images are SEM images of NHCR in Comparative Example 1, where a is the SEM image at 2 μm and b is the SEM image at 100 nm. Figure 9 The graph shows the electrochemical performance test results of the CR2032 coin cell in Comparative Example 1. Detailed Implementation

[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0022] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0023] Example 1 Tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon materials, such as Figure 1 As shown, its preparation method is as follows: 1) Disperse 3.3 g of zinc acetate dihydrate in 45 mL of deionized water, then add 12 g of sodium hydroxide. After stirring and clarifying, add 105 mL of glycerol and react for 30 minutes. Then pour the mixture into the liner of a reaction vessel for hydrothermal reaction at 150 °C for 20 h. Wash the precipitate with deionized water until neutral and dry at 80 °C to obtain rod-shaped zinc oxide. 2) Disperse 1.5 g of zinc oxide (stirred and sonicated for 30 minutes) in a mixed solution of 34 mL deionized water and 66 mL N,N-dimethylformamide; dissolve 7.2 g of dimethylimidazole in a mixed solution of 34 mL deionized water and 66 mL N,N-dimethylformamide. Add the latter to the former, then add 0.0286 g of phosphotungstic acid. Heat and stir in a water bath at 75 °C for 12 h to obtain a precipitate. Finally, centrifuge the precipitate once in the original solution and dry it at 80 °C to obtain a precursor with a rod-like structure (denoted as PTA@ZIF-8 / ZnO-150). 3) Place PTA@ZIF-8 / ZnO-150 in a tube furnace and heat it to 900℃ at a rate of 3℃ / min under an argon atmosphere. Hold the temperature for 2 hours and then allow it to cool naturally to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-150).

[0024] WC in this embodiment 1-x Scanning electron microscope (SEM) and transmission electron microscope (TEM) images of / NHCR-150 are as follows: Figure 2 As shown, the nitrogen adsorption-desorption curves are as follows: Figure 3 As shown.

[0025] Depend on Figure 2 It can be seen that WC 1-x / NHCR-150 exhibits a hollow rod-like structure, which is beneficial for increasing sulfur loading. (The last sentence appears to be incomplete and unrelated to the preceding text.) Figure 3 It can be seen that WC 1-x / NHCR-150 has a large specific surface area and abundant microporous / mesoporous structures, which are beneficial for providing space for sulfur to be contained and for sufficient contact between the electrolyte and the electrolyte.

[0026] A room-temperature sodium-sulfur battery cathode material was prepared using this tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material. The preparation method is as follows: 0.12g of the above WC 1-x / NHCR-150 and 0.13g of sublimed sulfur were dispersed in 15mL of carbon disulfide, ground in a fume hood until the carbon disulfide was completely volatilized, then transferred to a hydrothermal reactor, heated to 155℃, held at that temperature for 12h, and naturally cooled to room temperature to obtain the room temperature sodium-sulfur battery cathode material (denoted as S@WC). 1-x / NHCR-150).

[0027] The thermogravimetric analysis (TGA) curve of the room-temperature sodium-sulfur battery cathode material in this embodiment is as follows: Figure 4 As shown. By Figure 4 It can be seen that the sulfur content in the cathode material of the room temperature sodium-sulfur battery is 51 wt%.

[0028] A room-temperature sodium-sulfur battery was prepared using this room-temperature sodium-sulfur battery cathode material, and the preparation method is as follows: The above-mentioned room temperature sodium-sulfur battery positive electrode material was used to prepare a positive electrode sheet, and metallic sodium was used to prepare a negative electrode sheet. 1M NaClO4 dissolved in 5% fluoroethylene carbonate and ethylene carbonate / propylene carbonate (EC / DEC, 1:1 Vol.%, 5% FEC) was used as the electrolyte. The cells were assembled in an argon-filled glove box to obtain a button cell with the model number CR2032.

[0029] The electrochemical performance test results of the CR2032 button cell in this embodiment are as follows: Figure 5 As shown. By Figure 5 It can be seen that the CR2032 button cell exhibits high rate performance, achieving a discharge specific capacity of up to 433mAh / g even at a high discharge rate of 10C.

[0030] Example 2 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), add 0.043g of phosphotungstic acid.

[0031] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0032] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0033] WC in this embodiment 1-x SEM images of / NHCR-100, such as Figure 6 As shown.

[0034] Depend on Figure 6 It can be seen that WC 1-x / NHCR-100 has a hollow rod-like structure.

[0035] The electrochemical performance test results of the CR2032 button cell in this embodiment are as follows: Figure 7 As shown.

[0036] Depend on Figure 7 It can be seen that the CR2032 button cell has high rate performance, and can release a high discharge specific capacity of 382mAh / g at a discharge rate of 10C.

[0037] Example 3 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 1), a hydrothermal reaction is carried out at a temperature of 140°C for 20 hours.

[0038] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0039] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0040] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0041] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0042] Example 4 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 1), a hydrothermal reaction is carried out at a temperature of 140°C for 20 hours.

[0043] In step 2), add 0.043g of phosphotungstic acid.

[0044] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0045] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0046] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0047] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0048] Example 5 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 1), a hydrothermal reaction is carried out at a temperature of 160°C for 20 hours.

[0049] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0050] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0051] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0052] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0053] Example 6 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 1), a hydrothermal reaction is carried out at a temperature of 160°C for 20 hours.

[0054] In step 2), add 0.043g of phosphotungstic acid.

[0055] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0056] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0057] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0058] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0059] Example 7 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 5.78 g of dimethylimidazole was dissolved in a mixed solution of 34 mL of deionized water and 66 mL of N,N-dimethylformamide.

[0060] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0061] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0062] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0063] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0064] Example 8 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 5.78 g of dimethylimidazole was dissolved in a mixed solution of 34 mL of deionized water and 66 mL of N,N-dimethylformamide. Then, 0.043 g of phosphotungstic acid was added.

[0065] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0066] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0067] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0068] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0069] Example 9 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 8.67 g of dimethylimidazole was dissolved in a mixed solution of 34 mL of deionized water and 66 mL of N,N-dimethylformamide.

[0070] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0071] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0072] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0073] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0074] Example 10 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 8.67 g of dimethylimidazole was dissolved in a mixed solution of 34 mL of deionized water and 66 mL of N,N-dimethylformamide. Then, 0.043 g of phosphotungstic acid was added.

[0075] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0076] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0077] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0078] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0079] Example 11 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 1.5g of zinc oxide is dispersed (stirred and sonicated for 30 minutes) into a mixed solution of 50mL deionized water and 50mL N,N-dimethylformamide; 7.2g of dimethylimidazole is dissolved in a mixed solution of 50mL deionized water and 50mL N,N-dimethylformamide.

[0080] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0081] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0082] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0083] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0084] Example 12 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 1.5 g of zinc oxide is dispersed (stirred and sonicated for 30 minutes) in a mixed solution of 50 mL deionized water and 50 mL N,N-dimethylformamide; 7.2 g of dimethylimidazole is dissolved in a mixed solution of 50 mL deionized water and 50 mL N,N-dimethylformamide. After adding the latter to the former, 0.043 g of phosphotungstic acid is added.

[0085] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0086] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0087] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0088] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0089] Example 13 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), the mixture is heated and stirred in a water bath at a temperature of 70°C for a reaction time of 12 hours to obtain a precipitate.

[0090] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0091] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0092] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0093] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0094] Example 14 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 0.043 g of phosphotungstic acid was added. The mixture was heated and stirred in a water bath at 70 °C for 12 h to obtain a precipitate.

[0095] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0096] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0097] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0098] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0099] Example 15 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), the mixture is heated and stirred in a water bath at a temperature of 80°C for a reaction time of 12 hours to obtain a precipitate.

[0100] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0101] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0102] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0103] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0104] Example 16 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 0.043 g of phosphotungstic acid was added. The mixture was heated and stirred in a water bath at 80 °C for 12 h to obtain a precipitate.

[0105] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0106] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0107] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0108] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0109] Example 17 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), the mixture is heated and stirred in a water bath at a temperature of 75°C for a reaction time of 10 hours to obtain a precipitate.

[0110] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0111] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0112] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0113] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0114] Example 18 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 0.043 g of phosphotungstic acid was added. The mixture was heated and stirred in a water bath at 75 °C for 10 h to obtain a precipitate.

[0115] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0116] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0117] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0118] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 2.

[0119] Example 19 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), the mixture is heated and stirred in a water bath at a temperature of 75°C for a reaction time of 15 hours to obtain a precipitate.

[0120] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-150).

[0121] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0122] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0123] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0124] Example 20 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), 0.043 g of phosphotungstic acid was added. The mixture was heated and stirred in a water bath at 75 °C for 15 h to obtain a precipitate.

[0125] This yields nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide (denoted as WC). 1-x / NHCR-100).

[0126] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0127] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0128] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is similar to that of the CR2032 button cell assembled in Example 2.

[0129] Example 21 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 3), PTA@ZIF-8 / ZnO-150 is placed in a tube furnace and heated to 900℃ at a heating rate of 3℃ / min under a nitrogen atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-150).

[0130] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0131] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0132] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0133] Example 22 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), add 0.043g of phosphotungstic acid.

[0134] In step 3), PTA@ZIF-8 / ZnO-100 is placed in a tube furnace and heated to 900℃ at a heating rate of 3℃ / min under a nitrogen atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-100).

[0135] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0136] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0137] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 2.

[0138] Example 23 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 3), PTA@ZIF-8 / ZnO-150 is placed in a tube furnace and heated to 900℃ at a heating rate of 5℃ / min under an argon atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-150).

[0139] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0140] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0141] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0142] Example 24 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), add 0.043g of phosphotungstic acid.

[0143] In step 3), PTA@ZIF-8 / ZnO-100 is placed in a tube furnace and heated to 900℃ at a heating rate of 5℃ / min under an argon atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-100).

[0144] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0145] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0146] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 2.

[0147] Example 25 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 3), PTA@ZIF-8 / ZnO-150 is placed in a tube furnace and heated to 850°C at a heating rate of 3°C / min under an argon atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-150).

[0148] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0149] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0150] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0151] Example 26 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), add 0.043g of phosphotungstic acid.

[0152] In step 3), PTA@ZIF-8 / ZnO-100 is placed in a tube furnace and heated to 850°C at a heating rate of 3°C / min under an argon atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-100).

[0153] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0154] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0155] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 2.

[0156] Example 27 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 3), PTA@ZIF-8 / ZnO-150 is placed in a tube furnace and heated to 950°C at a heating rate of 3°C / min under an argon atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-150).

[0157] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0158] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0159] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0160] Example 28 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), add 0.043g of phosphotungstic acid.

[0161] In step 3), PTA@ZIF-8 / ZnO-100 is placed in a tube furnace and heated to 950°C at a heating rate of 3°C / min under an argon atmosphere. The temperature is held for 2 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-100).

[0162] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0163] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0164] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 2.

[0165] Example 29 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 3), PTA@ZIF-8 / ZnO-150 is placed in a tube furnace and heated to 900℃ at a heating rate of 3℃ / min under an argon atmosphere. The temperature is held for 1 hour and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-150).

[0166] After testing, the WC in this embodiment... 1-x The / NHCR-150 exhibits a hollow cubic structure.

[0167] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0168] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0169] Example 30 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), add 0.043g of phosphotungstic acid.

[0170] In step 3), PTA@ZIF-8 / ZnO-100 is placed in a tube furnace and heated to 900℃ at a heating rate of 3℃ / min under an argon atmosphere. The temperature is held for 1 hour, and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-100).

[0171] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0172] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0173] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 2.

[0174] Example 31 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 3), PTA@ZIF-8 / ZnO-150 is placed in a tube furnace and heated to 900℃ at a heating rate of 3℃ / min under an argon atmosphere. The temperature is held for 3 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-150).

[0175] After testing, the WC in this embodiment... 1-x / NHCR-150 exhibits a hollow rod-like structure.

[0176] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0177] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 1.

[0178] Example 32 The preparation method of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material differs from that in Example 1 as follows: In step 2), add 0.043g of phosphotungstic acid.

[0179] In step 3), PTA@ZIF-8 / ZnO-100 is placed in a tube furnace and heated to 900℃ at a heating rate of 3℃ / min under an argon atmosphere. The temperature is held for 3 hours and then naturally cooled to room temperature to obtain tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material (denoted as WC). 1-x / NHCR-100).

[0180] After testing, the WC in this embodiment... 1-x / NHCR-100 exhibits a hollow rod-like structure.

[0181] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0182] Tests showed that the performance of the CR2032 button cell assembled in this embodiment is close to that of the CR2032 button cell assembled in Example 2.

[0183] Comparative Example 1 The preparation method of nitrogen-doped hollow rod-shaped carbon material is as follows: 1) Disperse 3.3 g of zinc acetate dihydrate in 45 mL of deionized water, then add 12 g of sodium hydroxide. After stirring and clarifying, add 105 mL of glycerol and react for 30 minutes. Pour the mixture into the liner of a reaction vessel. Perform a hydrothermal reaction at 150 °C for 20 h. Wash the precipitate with deionized water until neutral and dry at 80 °C to obtain rod-shaped zinc oxide. 2) Disperse 1.5g of zinc oxide (stirred and sonicated for 30 minutes) in a mixed solution of 34mL deionized water and 66mL N,N-dimethylformamide; dissolve 7.2g of dimethylimidazole in a mixed solution of 34mL deionized water and 66mL N,N-dimethylformamide. Add the latter to the former. Heat and stir in a water bath at 75℃ for 12h to obtain a precipitate. Centrifuge the precipitate once in the original solution and dry it at 80℃ to obtain a precursor with a rod-like structure (denoted as ZIF-8 / ZnO). 3) Place ZIF-8 / ZnO in a tube furnace and heat it to 900℃ at a heating rate of 3℃ / min under an argon atmosphere. Hold the temperature for 2 hours and then cool it naturally to room temperature to obtain nitrogen-doped hollow rod-shaped carbon material (denoted as NHCR).

[0184] The SEM image of NHCR in this comparative example is shown below. Figure 8 As shown.

[0185] Depend on Figure 8 It can be seen that NHCR exhibits a hollow rod-like structure with relatively large pore size.

[0186] Room temperature sodium-sulfur battery cathode material was prepared according to the method in Example 1, and CR2032 button cell was assembled.

[0187] The electrochemical performance test results of the CR2032 button cell (denoted as S@NHCR) are as follows: Figure 9 As shown.

[0188] Depend on Figure 9 It is known that the CR2032 button cell has poor rate performance, with a discharge capacity of only 121 mAh / g at a discharge rate of 10C.

[0189] Therefore, the present invention utilizes the above-mentioned tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material and its preparation method and application, which is beneficial to the adsorption of polysulfides, can mitigate the shuttle effect, accelerate the conversion between sulfur and polysulfides, and has a simple preparation method and low production cost. The sodium-sulfur battery assembled after sublimation sulfur composite is made into a cathode material has excellent cycle stability and rate performance, and is suitable for large-scale application.

[0190] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing nitrogen-doped hollow rod-shaped carbon materials modified with tungsten carbide, characterized in that, Includes the following steps: S1. Disperse zinc acetate dihydrate and sodium hydroxide in deionized water according to the proportion, stir and mix, clarify and then add glycerol to carry out hydrothermal reaction to obtain zinc oxide with rod-shaped structure. S2. According to the proportion, zinc oxide, phosphotungstic acid and 2-methylimidazole obtained in S1 are dispersed in a mixed solution of deionized water and N,N-dimethylformamide, and a self-assembly reaction is carried out by water bath heating to obtain PTA@ZIF-8 / ZnO. S3. Place the PTA@ZIF-8 / ZnO obtained in S2 in an inert atmosphere and perform carbonization treatment to obtain nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide. In S2, the heating temperature of the water bath heating self-assembly reaction is 70~80℃, and the heating time is 10~15h.

2. The method for preparing tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material according to claim 1, characterized in that, In S1, the zinc acetate dihydrate is first dispersed in deionized water, then sodium hydroxide is added, stirred, and then glycerol is added; The ratio of zinc acetate dihydrate, deionized water, sodium hydroxide, and glycerol is 3.3g:45mL:12g:105mL.

3. The method for preparing tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material according to claim 1, characterized in that, In S1, the hydrothermal reaction specifically refers to: After adding glycerol, the mixture was allowed to stand for 30 minutes, then placed in a reaction vessel and reacted at 140-160°C for 20 hours to obtain a precipitate. The precipitate was washed with deionized water until neutral and dried to obtain rod-shaped zinc oxide.

4. The method for preparing tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material according to claim 1, characterized in that, In S2, the molar ratio of zinc oxide to phosphotungstic acid is 8.33~12.5:1; The molar ratio of zinc oxide to 2-methylimidazole is 1:4~6; The volume ratio of the deionized water to the N,N-dimethylformamide is 1:1 to 1.

95.

5. The method for preparing tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material according to claim 1, characterized in that, In S3, the inert atmosphere is either argon or nitrogen.

6. The method for preparing tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material according to claim 1, characterized in that, In S3, the specific conditions for the carbonization treatment are as follows: Heat to 850-950℃ at a heating rate of 3-5℃ / min, and hold for 1-3 hours.

7. The tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material prepared by the method for preparing tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material according to any one of claims 1 to 6.

8. The application of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material as described in claim 7 in the fabrication of room-temperature sodium-sulfur batteries, characterized in that, The room temperature sodium-sulfur battery includes a room temperature sodium-sulfur battery cathode material, wherein the preparation method of the room temperature sodium-sulfur battery cathode material includes the following steps: According to the proportion, the nitrogen-doped hollow rod-shaped carbon material modified with tungsten carbide and sublimed sulfur are dispersed in a volatile organic solvent, ground, heated to 155~165℃ and kept at that temperature for 6~12h to obtain a room temperature sodium-sulfur battery cathode material.

9. The application according to claim 8, characterized in that, The mass ratio of the tungsten carbide-modified nitrogen-doped hollow rod-shaped carbon material to the sublimed sulfur is 1:1.2~2.0.

Citation Information

Patent Citations

  • Molybdenum carbide modified hollow nitrogen-doped carbon particles as well as preparation method and application thereof

    CN114956038A

  • Hollow zinc sulfide nanotube for positive electrode of aqueous zinc-sulfur battery and preparation method of hollow zinc sulfide nanotube

    CN118993137A